Horton hatches the egg - Seuss, Dr. (New York, Random House, 1940)
When a lazy bird hatching an egg wants a vacation, she asks Horton, the elephant, to sit on her egg--which he does through all sorts of hazards until he is rewarded for doing what he said he would.
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
Library Journal
3.6
K-3
Keywords: Elephants -- Juvenile Fiction; Fantasy; Stories in rhyme; Elephants -- Fiction; Nonsense verses; Stories in rhyme